2016
DOI: 10.1111/cch.12341
|View full text |Cite
|
Sign up to set email alerts
|

Parents' perceptions of the services provided to children with cerebral palsy in the transition from preschool rehabilitation to school‐based services

Abstract: The transition from preschool to school-based services for children with CP is associated with a decrease in parents' perception of family centredness independent of the type of school. The transition in services has a negative impact on perceived family-centred practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 35 publications
2
16
0
7
Order By: Relevance
“…The results of this study demonstrated that the majority of families of children who are DHH accessing services from Hear for Kids were satisfied with the FCP they were receiving. Similar to other cross-sectional studies (Alsem et al, 2016;Cunningham & Rosenbaum, 2014;Kertoy et al, 2013;Siebes et al, 2007), the 'respectful and supportive care' subscale received the highest score and 'providing general information' the lowest. These findings are consistent with studies that have found that families accessing early intervention services, across a range of disabilities and countries, are least satisfied with the provision of general information regarding the child's disability and would like access to further unbiased information and resources (Cunningham & Rosenbaum, 2014).…”
Section: Discussionsupporting
confidence: 73%
“…The results of this study demonstrated that the majority of families of children who are DHH accessing services from Hear for Kids were satisfied with the FCP they were receiving. Similar to other cross-sectional studies (Alsem et al, 2016;Cunningham & Rosenbaum, 2014;Kertoy et al, 2013;Siebes et al, 2007), the 'respectful and supportive care' subscale received the highest score and 'providing general information' the lowest. These findings are consistent with studies that have found that families accessing early intervention services, across a range of disabilities and countries, are least satisfied with the provision of general information regarding the child's disability and would like access to further unbiased information and resources (Cunningham & Rosenbaum, 2014).…”
Section: Discussionsupporting
confidence: 73%
“…Nevertheless, they felt that the information they received from professionals was insufficient. Similarly, a study in the Netherlands reported that parents of children with cerebral palsy did not feel adequately informed, especially about services for their children and family (30).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it greatly affects parents' social relationships, stress levels and economic conditions, while moderately affects occupation, life with the partner, family relationships and individual welfare of parents. As confirmed by literature, the solicitude for a child with cerebral palsy may positively affect a parent's ability to create new social support networks, but the condition of such a child's care may adversely affect parents' physical health, social relationships, freedom and independence, family relationships and economic stability [14].…”
Section: Discussionmentioning
confidence: 92%
“…Recent literature on pediatric rehabilitation has shown that interventions focusing on children and their families can lead to satisfaction by the care, the well-being of parents and the reduction of parental anxiety [14]. Families involved in the care of their child have the opportunity to learn more about their child and their child's treatment options.…”
Section: Introductionmentioning
confidence: 99%